A flux-cored welding wire
By using flux-core welding wires containing low-carbon ferromanganese, silicon manganese alloy, aluminum-magnesium alloy, graphite, titanium iron and ice crystal in the welding of liquefied gas cylinders, the problem of difficult to meet the tensile strength, toughness and flatness of the weld during welding is solved, and efficient and high-quality welding results are achieved.
Patent Information
- Application Number
- CN202211625246.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The existing welding technology is difficult to meet the high requirements for the tensile strength, toughness and flatness of the weld during welding of liquefied gas cylinders.
A flux-core welding wire is used, which consists of a steel strip and a flux-core filled in the steel strip. The flux-core includes low-carbon ferromanganese, silicon manganese alloy, aluminum-magnesium alloy, graphite, titanium and ice crystal. Through the combination of these components, the content of impurities such as oxygen, hydrogen, nitrogen, sulfur in the weld is reduced, and the strength and toughness of the weld metal are improved.
It achieves high tensile strength, toughness and flatness of the weld, improves welding efficiency and product quality, and meets the high requirements for the welding of liquefied gas cylinders.
Smart Images

Figure GDA0005030308940000061 
Figure GDA0005030308940000071 
Figure GDA0005030308940000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, and in particular to a flux-cored welding wire. Background Art
[0002] Liquefied gas cylinders are already very popular in China. At present, liquefied gas cylinders are also being sought after in Southeast Asia and Africa, especially vehicle-mounted liquefied gas cylinders, which play a big role in people's lives. At present, the research on the manufacture of liquefied gas cylinders is still making continuous progress. The manufacture of liquefied gas cylinders is relatively simple overall, but because it is closely related to people's lives, its production safety is of great importance, so the production requirements of liquefied gas cylinders are relatively high.
[0003] Metal-electrode mixed gas shielded welding has become a high-quality, efficient and low-cost welding method. Due to its fast deposition speed, high production efficiency and easy motorization, it has the following characteristics compared with other welding methods: 1) high current density, fast deposition speed and high welding efficiency during welding; 2) low smoke and dust, and good working environment; 3) stable welding arc, less spatter and good weld formation. Applying metal-electrode mixed gas shielded welding to the welding of liquefied gas cylinders will greatly reduce environmental pollution, reduce labor intensity, improve production efficiency and reduce manufacturing costs. Liquefied gas cylinder welding requires a suitable welding wire that meets the requirements of high toughness, high welding strength and good flatness of liquefied gas cylinder welding. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a flux-cored welding wire to meet the requirements of good weld tensile strength and toughness and high flatness when welding liquefied gas cylinders.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides a flux-cored welding wire for welding liquefied gas cylinders, wherein the flux-cored welding wire comprises a steel strip and a flux core filled in the steel strip, wherein the flux core comprises the following components in percentage by mass: 6-9% low-carbon ferromanganese, 8-10% silicon-manganese alloy, 4-5% ferrosilicon, 5-7% aluminum-magnesium alloy, 1-2% graphite, 1-2% ferrotitanium, 6-8% cryolite, and the remainder is iron powder.
[0006] In one example of the present invention, the carbon content of the low carbon ferromanganese is ≤0.7wt%, the manganese content is ≥80wt%, the mass proportion of particles larger than 60 mesh is ≥80%, and the mass proportion of particles larger than 120 mesh is ≥50%.
[0007] In one example of the present invention, the ferrosilicon is 75# ferrosilicon, the silicon content in the ferrosilicon is ≥75wt%, the mass proportion of the ferrosilicon with a particle size greater than 60 mesh is ≥95%, and the mass proportion of the ferrosilicon with a particle size greater than 120 mesh is ≥40%.
[0008] In an example of the present invention, the carbon content in the graphite is ≥95wt%; and the particle size of the graphite is greater than 60 mesh.
[0009] In one example of the present invention, the content of sodium hexafluoroaluminate in the cryolite is ≥93wt%, and the mass proportion of particles larger than 80 mesh is ≥95%.
[0010] In one example of the present invention, the silicon content in the silicon-manganese alloy is 20-23wt%, and the manganese content is 62-67wt%; the mass proportion of particles larger than 40 mesh is ≥99%, the mass proportion of particles larger than 60 mesh is ≥90%, and the mass proportion of particles larger than 160 mesh is ≤50%.
[0011] In one example of the present invention, the titanium content in the titanium iron is 37-42wt%, and the silicon content is ≤5wt%; the mass proportion of particles larger than 40 mesh is ≥99%, the mass proportion of particles larger than 60 mesh is ≥90%, and the mass proportion of particles larger than 160 mesh is ≤50%.
[0012] In one example of the present invention, the aluminum content of the aluminum-magnesium alloy is 47-53wt%, and the magnesium content is ≥47wt%; the mass proportion of the aluminum-magnesium alloy with a particle size greater than 60 mesh is ≥95%, and the mass proportion of the aluminum-magnesium alloy with a particle size greater than 160 mesh is ≤30%.
[0013] In one example of the present invention, the steel strip is a low-carbon steel strip, in which the carbon content is ≤0.04wt%, the manganese content is 0.1-0.3wt%, the silicon content is ≤0.05wt%, the phosphorus content is ≤0.025wt%, the sulfur content is ≤0.02wt%, and the rest is iron.
[0014] In an example of the present invention, the weight of the flux core is 12% to 16% of the total weight of the flux cored welding wire; and the diameter of the flux cored welding wire is 1.2 mm to 1.6 mm.
[0015] The flux-cored welding wire of the present invention adds a certain proportion of aluminum-magnesium alloy, silicon-manganese alloy, titanium iron, low-carbon manganese iron and cryolite to reduce the oxygen content in the weld metal and improve the strength, crack resistance and low-temperature impact resistance of the weld metal; in addition, cryolite can also reduce the diffused hydrogen content inside the weld. Titanium and nitrogen elements combine to form titanium nitride, which can reduce the nitrogen content in the weld, and manganese and sulfur elements form manganese sulfide, which can reduce the sulfur content in the weld. Controlling impurities such as nitrogen, hydrogen, oxygen, sulfur, and phosphorus in the weld metal can improve the formation of acicular ferrite in the internal structure of the weld metal, thereby improving the toughness of the weld metal. DETAILED DESCRIPTION
[0016] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0017] It should be noted that "%" and "wt%" in this specification represent mass percentage, and "part" represents part by weight.
[0018] The flux-cored welding wire of the present invention is used for welding liquefied gas cylinders. The flux-cored welding wire comprises a steel strip and a flux core filled in the steel strip. The flux core comprises the following components in percentage by mass, and the weight proportion of each component is respectively: 6-9% of low-carbon ferromanganese, 8-10% of silicon-manganese alloy, 4-5% of ferrosilicon, 5-7% of aluminum-magnesium alloy, 1-2% of graphite, 1-2% of ferrotitanium, 6-8% of cryolite, and the balance is iron powder.
[0019] The functions of each component in the drug core are as follows:
[0020] Aluminum-magnesium alloy: The aluminum content of aluminum-magnesium alloy is 47-53wt%, and the magnesium content is ≥47wt%. It is the main strong deoxidizer in the formula of flux-cored welding wire. Adding aluminum-magnesium alloy powder to the formula makes it easy to realize arc spraying. The magnesium oxide produced by the reaction at high temperature enters the slag, which is beneficial to improve the basicity of the slag and the low-temperature toughness of the weld metal. With the increase of magnesium content, the burning loss of silicon and manganese elements is reduced, so the silicon and manganese content in the weld metal increases, and the weld surface is brighter. With the increase of aluminum-magnesium alloy, the arc spraying state of flux-cored welding wire is significantly improved, which has a good effect on welding spatter and weld formation, and is beneficial to ensure the smoothness of the weld surface. The mass percentage of aluminum-magnesium alloy with a particle size greater than 60 mesh is ≥95%, and the mass percentage of aluminum-magnesium alloy with a particle size greater than 160 mesh is ≤30%. The mass percentage of aluminum-magnesium alloy in the flux core of the present invention is 5-7%. For example, the mass percentage of aluminum-magnesium alloy can be any value within the range of 5-7%, such as 5%, 6% or 7%.
[0021] Silicon-manganese alloy: The silicon content in the silicon-manganese alloy is 20-23wt%, and the manganese content is 62-67wt%. As the main deoxidizer, the silicon-manganese alloy mainly participates in deoxidation and has an alloying effect. It is used to reduce the oxygen content of the weld metal, increase the strength and crack resistance of the weld metal, improve the elongation of the weld, and help improve the low-temperature impact toughness. The mass percentage of the silicon-manganese alloy with a particle size greater than 40 mesh is ≥99%, the mass percentage of the silicon-manganese alloy with a particle size greater than 60 mesh is ≥90%, and the mass percentage of the silicon-manganese alloy with a particle size greater than 160 mesh is ≤50%. The mass percentage of the silicon-manganese alloy in the flux core of the present invention is 8-10%. For example, the mass percentage of the silicon-manganese alloy can be any value within the range of 8-10%, such as 8%, 9% or 10%.
[0022] Ferrotitanium: The titanium content in ferrotitanium is 37-42wt%, and the silicon content is ≤5%. Its main function is to improve the toughness of the weld metal, and it has the functions of deoxidation, arc stabilization, promoting the transition of molten droplets in a mist form, and realizing the fine and bright weld formation. However, it is only beneficial to toughness within a very narrow content range. Too much content will reduce toughness. Ferrotitanium can promote the formation of acicular ferrite, refine grains, increase grain boundary area, improve the mechanical properties of materials, and have a good slag-making effect. Titanium can also form stable carbides. Adding titanium can also prevent intergranular corrosion, and titanium can be combined with nitrogen to form titanium nitride nucleation particles, reduce the nitrogen content of the weld, and further improve impact toughness. The mass percentage of ferrotitanium with a particle size greater than 40 mesh is ≥99%, the mass percentage of ferrotitanium with a particle size greater than 60 mesh is ≥90%, and the mass percentage of ferrotitanium with a particle size greater than 160 mesh is ≤50%. The mass percentage of ferrotitanium in the flux core of the present invention is 1-2%. For example, the mass percentage of ferrotitanium can be any value within the range of 1-2%, such as 1%, 1.5% or 2%.
[0023] Low carbon ferromanganese: The carbon content in low carbon ferromanganese is ≤0.7wt%, and the manganese content is ≥80wt%. Manganese is an important deoxidizer and also an important alloying agent for weld metal. It has an important influence on the strength and toughness of weld metal. Manganese can reduce the transformation temperature of austenite to ferrite and promote the formation of AF (acicular ferrite). The increase of manganese content can improve the low temperature impact toughness of the weld, but when the manganese content is too high, it will reduce the low temperature impact toughness of the weld. In addition, manganese can also form manganese sulfide with sulfur to reduce the impurity content of the weld. The mass percentage of low carbon ferromanganese with a particle size greater than 60 mesh is ≥80%, and the mass percentage of particles greater than 120 mesh is ≥50%. The mass percentage of low carbon ferromanganese in the flux core of the present invention is 6-9%. For example, the mass percentage of low carbon ferromanganese can be any value within the range of 6-9%, such as 6%, 8% or 9%.
[0024] Cryolite: The content of sodium hexafluoroaluminate in cryolite is ≥ 93wt%, and its main function is dehydrogenation, which reduces the content of diffused hydrogen inside the weld, and can also deoxidize and stabilize the arc. The mass percentage of cryolite with a particle size greater than 80 mesh is ≥ 95%. The mass percentage of cryolite in the flux core of the present invention is 6-8%, for example, the mass percentage of cryolite can be any value within the range of 6-8%, such as 6%, 7% or 8%.
[0025] Graphite: The carbon content in graphite is ≥ 95wt%. Graphite participates in the deoxidation reaction, reduces the oxygen content of the weld and transfers part of the carbon into the weld, increasing the yield strength and tensile strength. The particle size of the graphite is greater than 60 mesh. The mass percentage of graphite in the core of the present invention is 1-2%, for example, the mass percentage of graphite can be any value within the range of 1-2%, such as 1%, 1.5% or 2%.
[0026] Ferrosilicon: Ferrosilicon is 75# ferrosilicon, and the silicon content in ferrosilicon is ≥75wt%. Silicon element can participate in deoxidation and reduce the oxygen content in the weld. Silicon element can also enhance the fluidity of the molten pool, making the weld smoother. The mass percentage of ferrosilicon with a particle size greater than 60 mesh is ≥95%, and the mass percentage of ferrosilicon with a particle size greater than 120 mesh is ≥40%. The mass percentage of ferrosilicon in the flux core of the present invention is 4-5%, for example, the mass percentage of ferrosilicon can be any value within the range of 4-5%, such as 4%, 4.5% or 5%.
[0027] In one embodiment, the steel strip is a low-carbon steel strip, wherein the carbon content of the steel strip is ≤0.04wt%, the manganese content is 0.1-0.3wt%, the silicon content is ≤0.05wt%, the phosphorus content is ≤0.025wt%, the sulfur content is ≤0.02wt%, and the rest is iron.
[0028] In one embodiment, the filling rate of the flux core, i.e., the weight of the flux core, is 12% to 16% of the total weight of the flux cored welding wire; and the diameter of the flux cored welding wire is 1.2 mm to 1.6 mm. For example, the filling rate of the flux core can be any value within the range of 12% to 16%, such as 12%, 14%, or 16%, and the diameter of the flux cored welding wire can be any value within the range of 1.2 mm to 1.6 mm, such as 1.2 mm, 1.4 mm, or 1.6 mm.
[0029] The present invention is described in detail below through some specific examples. The drugs used in the following examples can all be obtained through common commercial means.
[0030] Example 1
[0031] The flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 6% low-carbon ferromanganese, 10% silicon-manganese alloy, 4% ferrosilicon, 7% aluminum-magnesium alloy, 1% graphite, 2% ferrotitanium, 7% cryolite, and the balance is iron powder. The flux-cored welding wire has a diameter of 1.2 mm and a filling rate of 14%.
[0032] Example 2
[0033] The flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 7% low-carbon ferromanganese, 8% silicon-manganese alloy, 4.5% ferrosilicon, 6% aluminum-magnesium alloy, 1.5% graphite, 1% ferrotitanium, 8% cryolite, and the balance is iron powder. The flux-cored welding wire has a diameter of 1.2 mm and a filling rate of 12%.
[0034] Example 3
[0035] The flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 9% low-carbon ferromanganese, 8% silicon-manganese alloy, 5% ferrosilicon, 6% aluminum-magnesium alloy, 2% graphite, 1.5% ferrotitanium, 6% cryolite, and the balance is iron powder. The total content of the components is 100%. The diameter of the flux-cored welding wire is 1.4 mm, and the filling rate is 15%.
[0036] Example 4
[0037] The flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 8% low-carbon ferromanganese, 9% silicon-manganese alloy, 4% ferrosilicon, 5% aluminum-magnesium alloy, 2% graphite, 2% ferrotitanium, 6% cryolite, and the balance is iron powder. The flux-cored welding wire has a diameter of 1.6 mm and a filling rate of 16%.
[0038] The component contents of the steel strip in the flux-cored welding wire of Examples 1 to 4 are shown in Table 1, and the contents of the components in the flux core are shown in Table 2. The welding performance of the flux-cored welding wire of Examples 1 to 4 was tested according to relevant standards and specifications, and the welding parameters are shown in Table 3, the deposited metal properties are shown in Table 4, and the bending performance test of the butt joint test plate of the flux-cored welding wire is shown in Table 5. During welding, the mixed gas (80% Ar + 20% CO2) is used for protection. When the two gases are used for mixed welding, their respective advantages can be fully utilized and their respective disadvantages can be avoided. The Ar gas component improves the quality of the welding surface and reduces the spatter caused by CO2. At the same time, the CO2 component enhances the stability of the arc and improves the heat conduction. In addition, the use of mixed gas welding reduces the reaction of CO and O2 decomposed by CO2 gas with elements such as manganese and silicon in the welding wire, so that more elements are integrated into the weld pool, which can be beneficial to improve the strength and toughness of the weld.
[0039] Table 1 Component contents of steel strips in Examples 1 to 4
[0040]
[0041] Table 2 Content of flux core components in flux cored welding wires of Examples 1 to 4
[0042]
[0043] Table 3 Welding parameters of deposited metal test plates of flux-cored welding wires of Examples 1 to 4
[0044]
[0045] Table 4: Deposited metal properties of flux-cored welding wires of Examples 1 to 4
[0046]
[0047] Table 5: Bending properties of butt joint test plates of flux-cored welding wires of Examples 1 to 4
[0048]
[0049] It can be seen from the test results of Table 4 and Table 5 that the flux-cored welding wire deposited metal of Examples 1 to 4 has good tensile strength, yield strength and elongation and good low-temperature impact resistance, and the flux-cored welding materials prepared by Examples 1 to 4 have good tensile strength and bending performance, and the joint performance is good. The flux-cored welding wire of the present invention is suitable for high-current welding, and its molten droplets are fine particles transition, spatter is small, the arc is stable, the weld surface is slag-free and shiny, and the post-weld grinding process is saved, which can not only improve the welding effect, but also ensure the beauty of the weld, and has good strength, elongation and impact toughness, and can have good pressure resistance, air tightness and fatigue resistance, and ensure the safe and reliable performance of the cylinder during use. Therefore, the flux-cored welding wire of the present invention is suitable for the welding of liquefied gas cylinders.
[0050] The flux-cored welding wire of the present invention adds a certain proportion of aluminum-magnesium alloy, silicon-manganese alloy, titanium iron, low-carbon manganese iron and cryolite to reduce the oxygen content in the weld metal and improve the strength, crack resistance and low-temperature impact resistance of the weld metal; in addition, cryolite can also reduce the diffused hydrogen content inside the weld. The titanium element and nitrogen element combine to form titanium nitride, which can reduce the nitrogen content in the weld, and the manganese element and sulfur element form manganese sulfide, which can reduce the sulfur content in the weld. Controlling impurities such as nitrogen, hydrogen, oxygen, sulfur, and phosphorus in the weld metal can increase the formation of acicular ferrite in the internal structure of the weld metal, thereby improving the toughness of the weld metal. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0051] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A flux-cored welding wire for welding liquefied gas cylinders, characterized in that: The flux-cored welding wire includes a steel strip and a flux core filled in the steel strip. The flux core includes the following components in percentage by mass: 6-9% low-carbon ferromanganese, 8-10% silicon-manganese alloy, 4-5% ferrosilicon, 5-7% aluminum-magnesium alloy, 1-2% graphite, 1-2% ferrotitanium, 6-8% cryolite, and the balance is iron powder. The weight of the flux core is 12%-16% of the total weight of the flux-cored welding wire.
2. The flux-cored welding wire according to claim 1, characterized in that: The low-carbon ferromanganese has a carbon content of ≤0.7wt%, a manganese content of ≥80wt%, a particle size greater than 60 meshes accounting for ≥80% by weight, and a particle size greater than 120 meshes accounting for ≥50% by weight.
3. The flux-cored welding wire according to claim 1, characterized in that: The ferrosilicon is 75# ferrosilicon, the silicon content in the ferrosilicon is ≥75wt%, the mass proportion of the ferrosilicon with a particle size greater than 60 mesh is ≥95%, and the mass proportion of the ferrosilicon with a particle size greater than 120 mesh is ≥40%.
4. The flux-cored welding wire according to claim 1, characterized in that: The carbon content in the graphite is ≥ 95wt%; The particle size of the graphite is greater than 60 mesh.
5. The flux-cored welding wire according to claim 1, characterized in that: The content of sodium hexafluoroaluminate in the cryolite is ≥93wt%, and the mass proportion of the particle size greater than 80 mesh is ≥95%.
6. The flux-cored welding wire according to claim 1, characterized in that: The silicon content of the silicon-manganese alloy is 20-23wt%, and the manganese content is 62-67wt%; the mass proportion of particles larger than 40 meshes is ≥99%, the mass proportion of particles larger than 60 meshes is ≥90%, and the mass proportion of particles larger than 160 meshes is ≤50%.
7. The flux-cored welding wire according to claim 1, characterized in that: The titanium content of the titanium iron is 37-42wt%, and the silicon content is ≤5wt%; the mass proportion of particles larger than 40 meshes is ≥99%, the mass proportion of particles larger than 60 meshes is ≥90%, and the mass proportion of particles larger than 160 meshes is ≤50%.
8. The flux-cored welding wire according to claim 1, characterized in that: The aluminum content of the aluminum-magnesium alloy is 47-53wt%, and the magnesium content is ≥47wt%; the mass proportion of the aluminum-magnesium alloy with a particle size greater than 60 mesh is ≥95%, and the mass proportion of the aluminum-magnesium alloy with a particle size greater than 160 mesh is ≤30%.
9. The flux-cored welding wire according to claim 1, characterized in that: The steel strip is a low-carbon steel strip, wherein the carbon content of the steel strip is ≤0.04wt%, the manganese content is 0.1-0.3wt%, the silicon content is ≤0.05wt%, the phosphorus content is ≤0.025wt%, the sulfur content is ≤0.02wt%, and the rest is iron.
10. The flux-cored welding wire according to claim 1, characterized in that: The diameter of the flux-cored welding wire is 1.2 mm to 1.6 mm.
Citation Information
Patent Citations
Metal powder type flux-cored wire for primer steel-plate corner welding
CN101450427A
High-toughness metal powder flux-cored wire for argon-rich shielded welding
CN111203673A